Growth Mindset as a Personal Preference Predicts Teachers’ Favorable Evaluation of Positive Education as an Imported Practice When Institutional and Normative Support for It Are Both Strong or Both Weak - Chan, Vincci; Chiu, Chi-yue; Lee, Sau-lai; Leung, Iris; Tong, Yuk-Yue (Frontiers in Psychology, 2020)
Past research on pathways to cultural influence on judgment has compared the explanatory power of personal preferences, perceived descriptive norms and institutionalization. Positive education is an education movement inspired by Western positive psychology. The present study examined how these factors jointly predict Hong Kong teachers’ evaluation of imported positive education programs in their schools. In a field study, we measured teachers’ personal endorsement of growth mindset (a positive psychology construct developed in the US) and their evaluation of adopting positive education programs in their schools. We also measured teachers’ perception of the extent of institutional and normative support for positive education in their schools. The results show that teachers’ personal preferences for growth mindset predict more favorable evaluation of positive education programs when institutional and normative support for positive education programs are both weak, or when they are both strong. We interpret these effects from the perspectives of the strong situation hypothesis and the intersubjective theory of culture.